Extraction of Organochlorine Pesticides from Honey using Dispersive Liquid-liquid Microextraction Technique and Determined by Gas Chromatography–electron Capture Detector - Na Ubol, Rattiya; Sommit, Nampu; Kanthiya, Pongsakorn (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 4 (2022): October-December 2022, 2022)
An effective sample pretreatment method namely dispersive liquid-liquid microextraction (DLLME) has been utilized for matrix removal from honey samples. The DLLME procedure in this study was carried out using toluene as an extraction solvent and acetonitrile as a dispersive solvent mixed in a centrifuge tube. Additionally, the analytical method of two types of organochlorine pesticides including lindane and dieldrin using gas chromatography equipped with electron capture detector (GC-ECD) has been validated for an effective quantification of these pesticides in honey samples. The parameters of validation such as linearity, precision, limit of detection, limit of quantification and recovery were evaluated. The experimental results presenting the linearity for lindane and dieldrin data (R 2 values ≥ 0.995) were in the range of 0.05-1000 ppb and 1-3000 ppb, respectively. The limit of detection (LOD) values of lindane and dieldrin were 0.18 and 0.27 ppb and the limit of quantification (LOQ) values were 0.60 and 0.87 ppb, respectively. The repeatability values expressed in terms of relative standard deviation (%RSD) ranged from 0.56-4.92%. The DLLME technique showed great potential as a sample preparation technique with the recovery percentage of  ≤ 104.40%. The pesticide residues were not detected in six honey samples collecting from Phayao Province, Thailand. Therefore, this proposed method is suitable for determination of pesticide residues in honey samples. Keywords:   Dispersive liquid-liquid microextraction (DLLME), Gas chromatography (GC), Electron capture detector (ECD), Organochlorine pesticides, Honey